Genetic landscape in Russian patients with familial left ventricular noncompaction - Meshkov, Alexey N.; Myasnikov, Roman P.; Kiseleva, Anna V.; Kulikova, Olga V.; Sotnikova, Evgeniia A.; Kudryavtseva, Maria M.; Zharikova, Anastasia A.; Koretskiy, Sergey N.; Mershina, Elena A.; Ramensky, Vasily E.; Zaicenoka, Marija; Vyatkin, Yuri V.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Left ventricular noncompaction (LVNC) cardiomyopathy is a disorder that can be complicated by heart failure, arrhythmias, thromboembolism, and sudden cardiac death. The aim of this study is to clarify the genetic landscape of LVNC in a large cohort of well-phenotyped Russian patients with LVNC, including 48 families (n=214). The genetic testing included next generation sequencing and genetic classification according to ACMG guidelines and allowed to identify 55 alleles of 54 pathogenic and likely pathogenic variants in 24 genes, with the largest number in the MYH7 and TTN genes. A significant proportion of variants —8 of 54 (14.8%)—have not been described earlier in other populations and may be specific to LVNC patients in Russia. In LVNC patients, the presence of each subsequent variant is associated with increased odds of having more severe LVNC subtypes than isolated LVNC with preserved EF. The corresponding odds ratio is 2.77 (1.37–7.37; p <0.001) per variant after adjustment for sex, age, and family. Overall, the genetic analysis of LVNC patients, accompanied by cardiomyopathy-related family history analysis, resulted in a high diagnostic yield of 89.6%. These results suggest that genetic screening should be applied to the diagnosis and prognosis of LVNC patients.